Nano-porous activated carbon from sugarcane waste for supercapacitor application. (December 2015) - Jain, Amrita; Tripathi, S.K.
Highlights: BCT with specific surface area of 400 m 2  g −1 was synthesized using chemical activation technique. XRD studies of BCT confirm the formation of graphite and amorphous C. EDLC cell has been successfully fabricated and characterized using BCT as an electrode material with ionic liquid based polymer gel electrolytes having good energy and power density. Abstract: Low cost with high specific capacitance and energy density is the critical and main requirement for practical supercapacitors. In the present work, nano porous activated carbon having specific surface area of 400 m 2  g −1 from sugarcane waste (bagasse) has been synthesized and characterized as an electrode material for supercapacitor applications using ionic liquid based polymer gel electrolytes. The fabricated cell shows the overall specific capacitance of 372 mF cm −2 which is equivalent to single electrode specific capacitance of 248 F g −1 . The corresponding energy and power density of 16.3 Wh kg −1 and 1.66 kW kg −1 were achieved for EDLCs.